Copper-catalyzed tandem arylation–cyclization of 2-alkynylaryl isothiocyanates with diaryliodonium salts: an efficient synthesis of thiochromeno[2, 3-b]indoles. Issue 7 (24th May 2016) - Wen, Li-Rong; Shen, Qiang-Yu; Guo, Wei-Si; Li, Ming
Abstract : A Cu-catalyzed arylation–cyclization approach is developed for the synthesis of thiochromeno[2, 3- b ]indoles through the S -arylation, 5- endo-trig cyclization, and Friedel–Crafts-type cyclization sequence. Abstract : A catalytic tandem arylation–cyclization approach using 2-alkynylphenyl isothiocyanates with diaryliodonium salts is described. The reaction is performed under mild conditions and thiochromeno[2, 3- b ]indoles are obtained in moderate to good yields. This tandem protocol involves chemoselective S -arylation, regioselective 5- endo-trig cyclization and Friedel–Crafts-type cyclization processes. Two C–C bonds, one C–S bond, and two heterocyclic rings are formed in a single step. Preliminary mechanistic studies indicate that a carbocation mechanism is involved.